META ANALISIS PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS - Wirda Taufik; Lufri Lufri; Zulyusri Zulyusri; Fitri Arsih (Bioilmi: Jurnal Pendidikan, 2022)
This study aims to analyze previously published studies so as to obtain a summary of the effect of the Problem Based Learning (PBL) learning model on students' critical thinking abilities in learning biology. This research is an experimental research with a meta-analysis technique. This meta-analysis technique is carried out in several steps, namely (1) determining the research topic, (2) determining the period of the article to be used, (3) searching for scientific articles that will support the research, (4) reading, determining, and analyzing the article to be used, (5) analyze, process, and conclude the data obtained. The research method used in this research is a survey of scientific research articles and other scientific publications. The effect of studies that have applied the problem-based learning model is analyzed using meta-analysis techniques. The findings of this study reveal that the problem-based learning model has an effect on students' critical thinking skills in learning biology. This can be seen from the results of a meta-analysis study with an average effect size of 0.52 on the moderate criteria.